Content Analysis Of Vitamin C In Fresh And Processed Moringa Trees By Spectrophotometry And Iodometric Titration Methods - S. Sarah; R.S. Murthy; A. P. Sugiarto; S. Sariyati; E. Priyambodo (Universitas Negeri Yogyakarta, 2018)
The aims of this research were to examine the vitamin C content found in fresh and processed moringa trees and to know the method/ stage used to analyze the vitamin C content found in fresh and processed moringa trees. This research uses two methods namely spectrophotometric method and iodometry titration method. Initial stage prepare the sample of moringa, which were moringa leaf, moringa stem and moringa seed. The results showed that at the wavelength of 600 nm and after the iodometric titration, all the moringa samples (leaves, stems and seeds) contain vitamin C. Both of this two methods, spectrophotometry and iodometric titration, is able to analysis vitamin C in Morianga trees.